Impact of Centralized Management of Bariatric Surgery Complications on 90-day Mortality. Issue 5 (November 2018) - Caiazzo, Robert; Baud, Gregory; Clément, Guillaume; Lenne, Xavier; Torres, Fanelly; Dezfoulian, Guelareh; Lebuffe, Gilles; Kipnis, Eric; Dervaux, Benoit; Pattou, Francois
Abstract : Background and Aims: The potential benefit of the centralization of Bariatric surgery (BS) remains debated. The aim of this study was to evaluate the impact on 90-day mortality of an innovative organization aiming at centralizing the care of severe postoperative complications of BS. Study Design: The centralization of care for postoperative complication after BS was implemented by French Authorities in 2013 in the Nord-Pas-de-Calais Region, France. This unique formalized network (OSEAN), coordinated by 1 tertiary referral center, enrolled all regional institutions performing bariatric surgery. Data were extracted from the medico-administrative database providing information on all patients undergoing BS between 2009 and 2016 in OSEAN (n = 22, 928) and in Rest of France (n = 288, 942). The primary outcome was the evolution of 90-day mortality before and after the implementation of this policy. Rest of France was used as a control group to adjust the results to improvement with time of BS outcomes. Results: The numbers of primary procedure and reoperations increased similarly before and after 2013 within OSEAN and in Rest of France. The 90-day mortality rate became significantly lower within OSEAN than in the rest of France after 2013 (0.03% vs 0.08%, P < 0.01). This difference was confirmed in multivariate analysis after adjustment to the procedure specific mortality ( P < 0.04). The reduction of 90-day mortality was most visible for sleeve gastrectomy. Conclusion: The implementation of centralized care for early postoperative complications after BS in OSEAN was associated with reduced 90-day mortality. Our results indicate that this reduction was not due to a lower incidence of complications but to the improvement of their management. Abstract : Supplemental Digital Content is available in the text